Current and future approaches to treat graft failure after allogeneic hematopoietic stem cell transplantation. (January 2014) - Locatelli, Franco; Lucarelli, Barbarella; Merli, Pietro
<x xml:space="preserve">Abstract</x> Introduction: One significant obstacle to the success of allogeneic hematopoietic stem cell transplantation (HSCT) is represented by graft failure, defined as either lack of initial engraftment of donor cells (primary graft failure) or loss of donor cells after initial engraftment (secondary graft failure). Graft failure mediated by host immune cells attacking donor stem cells is named graft rejection. Factors associated with graft failure include HLA disparity in the donor/recipient pair, underlying disease, viral infections, type of conditioning regimen and stem cell source employed. Areas covered: In this article, the experts summarize current approaches to treat graft failure/rejection after HSCT, and they discuss new strategies of graft manipulation and immune therapy of particular interest for preventing/treating this complication. Expert opinion: A limited array of options is available to treat graft failure. The experts believe that re-transplantation from another donor or the same donor (if there is no evidence of immunologically mediated graft failure) is the treatment of choice for patients with primary graft failure or acute graft rejection. The experts think that strategies based on innovative approaches of graft manipulation, new agents or cellular therapies could render in the future graft failure a much less relevant problem for HSCT recipients.